A Study of E-Services of Bank with Special Reference to Private Banks, Ahmednagar - Nimbalkar, Atul Arun; Deodhar, Nachiket (International Research Journal of Management, IT & Social Sciences, 2015)
E-banking means electronic banking which is popularly known as anywhere banking. Electronic banking also known as EFT (electronic Fund Transfer) means transfer amount online from one account to another account rather by using physical cheque. Information technology has taken important place in the future development of financial service, specially banking sector transaction are affected more than any other financial provider groups. Increased use of mobile services and use of internet as a new distribution channel for banking transactions and international trading requires more attention towards e-banking security against fraudulent activities. The development and the increasing progress that is being experienced in the Information and Communication Technology have brought about a lot of changes in almost all facets of life. In the Banking Industry, it has been in the form of online banking, which is now replacing the traditional banking practice. Although it is proving boon to all sectors especially to all types of customers and financial sector but its growing use without awareness has also attracted many crimes and frauds. Through this paper, it is tried tom discuss about growth of E-banking along with growing challenges of risk & Insecurity. Emphasis is given on awareness to be given to E-banking users and establishment of more security measures to avoid chances of misappropriation of funds and cybercrimes. Online banking has a lot of benefits which add value to customersâ satisfaction in terms of better quality of service offerings and at the same time enable the banks gain more competitive advantage over other competitors. This paper discusses some challenges in an emerging economy and benefits of E-banking.